2021
DOI: 10.1021/acs.jpclett.1c03609
|View full text |Cite
|
Sign up to set email alerts
|

Au with sp3 Hybridization in Li5AuP2

Abstract: The achievement of new bonding patterns of atoms in compounds is of great importance, which usually induces interesting physical and chemical properties. Rich oxidation states, diverse bonding types, and unique aurophilic attraction endow gold (Au) as a distinctive element. Here we report that a pressure-induced Li5AuP2, identified by a swarm intelligence-based structural prediction, becomes the first example of Au with sp3 hybridization. The most remarkable feature of Li5AuP2 is that it contains various frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The interaction of Li, P, and Au at high pressure stabilizes the compounds with unique bonding patterns and features owing to the wider stoichiometry and synergetic charge transfer of ternary compounds . In that same work, Zhang et al revealed exciting properties, such as sp 3 hybridizations and bonding patterns, for the Li 5 AuP 2 compound at 25 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction of Li, P, and Au at high pressure stabilizes the compounds with unique bonding patterns and features owing to the wider stoichiometry and synergetic charge transfer of ternary compounds . In that same work, Zhang et al revealed exciting properties, such as sp 3 hybridizations and bonding patterns, for the Li 5 AuP 2 compound at 25 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is shown that Au can acquire a 6p-element characteristic by gaining electrons from the covalent tetrahedral configuration of other atoms with an sp 3 hybridization. , It has also been reported that the reaction of Li with Au and P under high pressure leads to extraordinary negative oxidation of Au. The interaction of Li, P, and Au at high pressure stabilizes the compounds with unique bonding patterns and features owing to the wider stoichiometry and synergetic charge transfer of ternary compounds . In that same work, Zhang et al revealed exciting properties, such as sp 3 hybridizations and bonding patterns, for the Li 5 AuP 2 compound at 25 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations